The Effects of Audit Committee Characteristics on Financial Distress in Banking Sector Companies Listing in Indonesia Stock Exchange 2018-2020 - Farah Aghniya ‘Ilmi; Nasyiah Hasanah Purnomowati (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2023)
This study aims to examine the effect of characteristics of the audit committee on financial distress. The source of data in this research is obtained from reports annual banking companies listed on the Indonesian Directory Exchange (IDX) during the period 2018-2020. Based on the purposive sampling method, the number of sample in this research is 38 samples of companies. The springate method is used to calculate financial distress in this research. Hypothesis testing in research this method uses multiple linear regression analysis with the EViews 9 program. The findings in this research are that the frequency of audit committee meetings affects financial distress, but shows that the size of the audit committee, the educational background of the audit committee and the gender diversity of the audit committee do not affect the financial distress.